Does short-term montelukast treatment cause sleep problems or psychiatric problems in children? A preliminary study - Emre Donmez, Yunus; Cakmak Karaer, Isil (Annals of Medical Research, 2021)
Aim: Montelukast is one of the treatment choices for symptomatic allergic rhinitis and asthma in children. Various researches emphasized that montelukast use causes neuropsychiatric side effects. The aim of this study was to investigate the effect of short-term montelukast use on children’s sleep habits, and whether sleep-related problems and psychiatric problems may occur.Material and Methods: This prospective study was conducted with 30 children. Psychiatric disorders and symptoms, sleep habits, sleep-related problems were evaluated before the use of montelukast. All of these evaluations were repeated at 4th and 8th week of treatment. Psychiatric assessment was performed with the Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version – Turkish. Sleep habits, sleep-related problems were assessed using the Children Sleep Habits Questionnaire Short Form (CSHQ-S) and the Pediatric Sleep Questionnaire (PSQ).Results: According to the psychiatric assessment, no psychiatric disease or symptom was identified before treatment and at the 4th and 8th week of treatment. The CSHQ-S and PSQ responses were evaluated and there was no significant difference between results obtained before treatment and at the 4th and 8th weeks of treatment.Conclusion: The results revealed that short-term montelukast use is safe and do not cause changes sleep habits, sleep-related problems or psychiatric problems in children. Long-term follow-up studies with high numbers of participants are needed to test these results and evaluate the possible neuropsychiatric side effects of long-term montelukast use.